2013
DOI: 10.1002/ijc.28050
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 L1 and L2 DNA methylation predicts high‐grade cervical intraepithelial neoplasia in women with mildly abnormal cervical cytology

Abstract: DNA methylation changes in human papillomavirus type 16 (HPV16) DNA are common and might be important for identifying women at increased risk of cervical cancer. Using recently published data from Costa Rica we developed a classification score to differentiate women with cervical intraepithelial neoplasia grade 2 or 3 (CIN2/3) from those with no evident high-grade lesions. Here, we aim to investigate the performance of the score using data from the UK. Exfoliated cervical cells at baseline and 6-months follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 33 publications
(75 reference statements)
5
98
1
Order By: Relevance
“…HPV16 L1 assays were done as previously described. 16 For EPB41L3 and LMX1A, the primers were designed using PyroMark Assay Design software version 2.0.1.15 (Qiagen). 21 The methods for amplification and pyrosequencing and the associated quality control procedures have been described in detail elsewhere.…”
Section: Methylation Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…HPV16 L1 assays were done as previously described. 16 For EPB41L3 and LMX1A, the primers were designed using PyroMark Assay Design software version 2.0.1.15 (Qiagen). 21 The methods for amplification and pyrosequencing and the associated quality control procedures have been described in detail elsewhere.…”
Section: Methylation Assaymentioning
confidence: 99%
“…21 The methods for amplification and pyrosequencing and the associated quality control procedures have been described in detail elsewhere. 16,18,21 …”
Section: Methylation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…These epigenetic differences can be accurately measured by molecular methods, and are linked with the development of a variety of cancers [10]. We and other research groups have observed that measurement of differential methylation of certain HPV CpG sites is useful for stratifying HPV type-specific risk [8,[11][12][13]19]. Additionally, methylation of CpGs in the promoters or introns of human genes has shown some value [5,6,9,14,20].…”
Section: Introductionmentioning
confidence: 99%